Daily Intake of Probiotics with High IFN-γ/IL-10 Ratio Increases the Cytotoxicity of Human Natural Killer Cells: A Personalized Probiotic Approach - Yu-Hsuan Ho; Yu-Chiu Lu; Hung-Cheng Chang; Shin-Yi Lee; Min-Fen Tsai; Yu-Ting Huang; Ting-Yuan Hsu (Journal of Immunology Research)
A personalized probiotic microfluidic chip system has been established and used to screen the probiotics which had the highest value of IFN-γ/IL-10 or IL-10/IFN-γ among six probiotics, including L. paracasei BRAP01, L. acidophilus AD300, B. longum BA100, E. faecium BR0085, L. rhamnosus AD500, and L. reuteri BR101. One hundred volunteers were included and their PBMCs were collected and stimulated by the six probiotics. People who belonged to the IFN-γ group took the probiotics that exerted the highest ratio of IFN-γ/IL-10 and vice versa in IL-10 group. A significant increase in NK cytotoxicity of 69 volunteers in the IFN-γ group was observed compared to the IL-10 group (n=21) and control group (n=10). The result also showed that L. paracasei BRAP01 and L. acidophilus AD300 were the two dominant inducers in IFN-γ group which yielded higher value of IFN-γ/IL-10 than the other 4 probiotics, while L. reuteri BR101 was the most effective agent on the ratio of IL-10/IFN-γ in the IL-10 group. Our finding highlighted the concept of personalized probiotics and also provided a good foundation to investigate the probiotics with NK activity.